REGULATION OF ALLERGEN-INDUCED UPPER AIRWAY INFLAMMATION BY TOPICAL CORTICOSTEROID AND RELATIONSHIP TO ALARMIN EXPRESSION IN ALLERGIC RHINITIS - Omer, Hafsa (My University, 2024)
Allergic rhinitis (AR) is a comorbidity in asthmatic patients and characterized by type 2 (T2) airway inflammation and expression of epithelial alarmins (interleukin (IL) 25, 33 and thymic stromal lymphopoietin (TSLP). In 10 mild allergic asthmatics with AR, we examined the effect of 2 weeks intranasal corticosteroid treatment with triamcinolone 220 µg BID on the regulation of T2 allergic responses to nasal allergen challenge (NAC), with a focus on alarmin cytokines in the upper airways. NAC increased total nasal symptom scores (TNSS) and reduced peak nasal inspiratory flow rate (PNIF) over the 7-hour measurement period. Eosinophil numbers increased at 24 hours post allergen in nasal biopsies. In nasal lavage, eosinophils and T2 cytokines IL-4, IL-5 and IL-13 increased at 7 and 24 hours post-allergen (p<0.05), and alarmin cytokines IL-25 and TSLP numerically increased above baseline at 7 hours post-allergen. IL-33-positive cells in nasal tissue decreased 24 hours post-NAC (p<0.05), but there was no change in the number of cells immunopositive for IL-25 or TSLP. INCS treatment for 2 weeks significantly attenuated allergen-induced changes in TNSS and PNIF, and inhibited allergen-induced eosinophils and T2 cytokines IL-4, IL-5, and IL-13 in the nasal lavage (p<0.05). INCS treatment had no effect on the number of alarmin immune-positive cells in nasal tissue. A consistent numerical reduction of IL-25 and TSLP levels in nasal lavage measured post-allergen with INCS versus placebo provides some evidence that these alarmin cytokines may be regulated by corticosteroids. Power calculations indicated that a doubling of the sample size would be needed to adequately test the effect of intranasal corticosteroid on alarmin levels in nasal lavage, thus larger studies will be needed to further examine the effects of corticosteroids on alarmin production in upper airways.